PENGARUH HOLDING TIME PADA BAJA ST 40 DENGAN PENGELASAN FCAW TERHADAP UJI TARIK DAN KEKERASAN - Hyang Adhyawantara; Nur Yanu Nugroho (Fakultas Sains dan Teknologi Universitas Karimun, 2023)
Welding is a process of joining metal objects using heat energy. In the welding process there is a problem that arises due to the uneven use of heat energy, namely residual stress, residual stress can cause cracks or defects in the weld. To reduce the risk of residual stresses forming in the joint area (HAZ) it can be carried out with the Post weld heat treatment (PWHT) process or the heat treatment process on the material after undergoing the welding process. This research was conducted to determine the effect of PWHT holding time variations on mechanical properties and also aims to determine how much holding time is appropriate for ST40 steel. In this study the PWHT temperature used was 875º C with 3 variations of holding time (45 minutes, 60 minutes and 75 minutes). Welding uses the FCAW (Flux-Cored Arc Welding) method with a 60º V seam and 1G position. Welding results are tested by tensile test and hardness test. From the results of the tensile test the best value was obtained at 60 minutes Holding Time of 384.5 MPa. The best hardness value was obtained by Holding Time 75 minutes of 137.8 HVN in the weld metal area.